Oncogenic mutations in histologically normal endometrium: the new normal? - Lac, Vivian; Nazeran, Tayyebeh M; Tessier‐Cloutier, Basile; Aguirre‐Hernandez, Rosalia; Albert, Arianne; Lum, Amy; Khattra, Jaswinder; Praetorius, Teresa; Mason, Madeline; Chiu, Derek; Köbel, Martin; Yong, Paul J; et al. (The Journal of pathology, 2019)
The advent of next generation sequencing has vastly improved the resolution of mutation detection, thereby both increasing the resolution of the analysis of cancer tissues and shining light on the existence of somatic driver mutations in normal tissues, even in the absence of cancer. Studies have described somatic driver mutations in normal skin, blood, peritoneal washings, and esophageal epithelium. Such findings prompt speculation on whether such mutations exist in other tissues, such as the eutopic endometrium in particular, due to the highly regenerative nature of the endometrium and the recent observation of recurrent somatic driver mutations in deep infiltrating and iatrogenic endometriosis (tissues believed to be derived from the eutopic endometrium) by our group and others. In the current study we investigated the presence of somatic driver mutations in histologically normal endometrium from women lacking evidence of gynecologic malignancy or endometrial hyperplasia. Twenty‐five women who underwent hysterectomies and 85 women who underwent endometrial biopsies were included in this study. Formalin‐fixed, paraffin‐embedded tissue specimens were analyzed by means of targeted sequencing followed by orthogonal validation with droplet digital PCR. PTEN and ARID1A immunohistochemistry (IHC) was also performed as surrogates for inactivating mutations in the respective genes. Overall, we observed somatic driver‐like events in over 50% of normal endometrial samples analyzed, including hotspot mutations in KRAS, PIK3CA, and FGFR2 as well as PTEN‐loss by IHC. Analysis of anterior and posterior samplings collected from women who underwent hysterectomies was consistent with the presence of somatic driver mutations within clonal pockets spread throughout the uterus. The prevalence of such oncogenic mutations also increased with age (OR: 1.05 [95% CI: 1.00–1.10], p = 0.035). These findings have implications on our understanding of aging and so‐called ‘normal tissues’, thereby necessitating caution in the utilization of mutation‐based early detection tools for endometrial or other cancers. © 2019 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.